2013
DOI: 10.3174/ajnr.a3710
|View full text |Cite
|
Sign up to set email alerts
|

CFD: Computational Fluid Dynamics or Confounding Factor Dissemination? The Role of Hemodynamics in Intracranial Aneurysm Rupture Risk Assessment

Abstract: SUMMARY:Image-based computational fluid dynamics holds a prominent position in the evaluation of intracranial aneurysms, especially as a promising tool to stratify rupture risk. Current computational fluid dynamics findings correlating both high and low wall shear stress with intracranial aneurysm growth and rupture puzzle researchers and clinicians alike. These conflicting findings may stem from inconsistent parameter definitions, small datasets, and intrinsic complexities in intracranial aneurysm growth and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
117
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(117 citation statements)
references
References 59 publications
(106 reference statements)
0
117
0
Order By: Relevance
“…Both studies agreed that ruptured aneurysms present complex flow structures and concentrated inflow. Recently, Meng et al 12 and Xiang et al 13 published a 2-part review summarizing the various criteria for rupture status predictions and introducing a hypothesis that both high and low WSS might lead to aneurysm rupture.…”
Section: Abbreviationsmentioning
confidence: 99%
“…Both studies agreed that ruptured aneurysms present complex flow structures and concentrated inflow. Recently, Meng et al 12 and Xiang et al 13 published a 2-part review summarizing the various criteria for rupture status predictions and introducing a hypothesis that both high and low WSS might lead to aneurysm rupture.…”
Section: Abbreviationsmentioning
confidence: 99%
“…[1][2][3] Using different approaches, a number of recent studies have demonstrated the feasibility of quantitative flow parameter measurement by using flat detector DSA. [4][5][6][7] Compared with optical flow methods and computer fluid dynamics simulations, flow parameter analysis with the time-attenuation curve (TDC) of DSA images is less demanding in terms of computer power and processing time. 8,9 Clinically, TDCs are used to assess the "real-time" peritherapeutic hemodynamics of various vascular disorders in an angiography suite.…”
mentioning
confidence: 99%
“…Large discrepancies were observed between the results with the non-Newtonian model with higher viscosity and those with the Newtonian model for several parameters, especially MWSS and NWSS, where NWSS is the WSS value normalized by WSS on the parent artery. Data are typically normalized so that the results for different patients can be compared when a CFD analysis is performed using the same inflow conditions [27]. Our results show that the differences in the ratios between the Newtonian and non-Newtonian models were greater for the normalized WSS than for the non-normalized WSS in case A (the smallest aneurysm).…”
Section: Discussionmentioning
confidence: 83%